Cyst Nematode (Heterodera glycines) Problems in Soybean (Glycine max L.) Crops and Its Management - Gebissa Yigezu Wendimu (Advances in Agriculture)
Soybean is a leguminous crop that originated from Southeast Asia, and it was domesticated in the northeastern parts of China. Recently, it has been highly produced in the United States of America, Brazil, and Argentina for cooking oil, protein, fiber and for the manufacturing of plastics, lubricants, candles, varnishes, soaps, and biodiesel. Nevertheless, in warm, moist, sandy soil conditions, its production is highly challenged by soybean cyst nematodes (Heterodera glycines). It caused more than 30% of soybean yield loss either alone or associated with other soybean pests under suitable environmental conditions. The second-stage juvenile (J2) of this pest inserted its stylet and penetrated into the cells to get its nourishment, shelter, and reproduction site on the soybean roots. Economically, the damage it caused was highly important because it had a wide host range and lacked adequate management methods. Hence, the reason behind the writing of this chapter is to explore the different published scientific papers related to soybean cyst nematode’s economic importance, distribution, symptoms, biology, life cycle, interaction with other pathogens, different management approaches, and its prospects. This chapter shall also embrace the advanced biotechnological innovations that help in achieving effective soybean cyst nematode management that will mitigate its infections in soybean production and will also serve as an asset for the researchers. This review chapter, in addition, plays a vital role in exploring necessary information concerning soybean cyst nematode management.